School Staff and Youth Perspectives of Tier 1 Restorative Practices Classroom Circles. Issue 1 (2nd January 2022) - Garnett, Bernice Raveche; Kervick, Colby T.; Moore, Mika; Ballysingh, Tracy A.; Smith, Lance C.
Abstract: This case study describes the experiences and perceptions of school staff and students participating in restorative practices (RP) community building circles during the first year of school-wide RP implementation. Data sources include (a) beginning- and end-of-year surveys of school staff perspectives and experiences with implementing RP, (b) semistructured interviews conducted with 17 school staff, and (c) surveys of third- to fifth-grade ( N = 107) students regarding their experiences participating in RP classroom circles. Across all data sources, the connection between community building circles and social–emotional learning (SEL) was evident and well articulated. Additionally, students and staff highlighted challenges in circle participation, equitable circle accessibility for all students, and tensions between RP and school discipline. The promise of RP to support SEL curriculum may only be realized if RP implementation is designed as a school-wide system to promote social development for both students and the adults who serve them.